Von Schluss zu Schluss: Die Entwicklung frühchristlicher Erinnerungsarbeit nach Joh 20,30–31 und Joh 21,24–25 - Witetschek, Stephan Joseph (Biblische Zeitschrift, 2024)
John 21 is widely regarded as a secondary addition to the Gospel of John. The most important indication for this is the conclusion John 20:30–31, which may appear obsolete in view of the final conclusion John 21:24–25. Both conclusions, however, provide interesting insights into the hermeneutical positions of their respective authors in the development of Christian collective memories with regard to the deliberate selection of relevant Jesus traditions, the transition from oral tradition to literary writing, and the personalization of memory, attached to the Beloved Disciple. Based on understanding them as self-reflective documents of collective memory, the comparison of these two conclusions makes it possible to delineate two different stages in the textualization and literarization of Jesus tradition and to define their respective places on the map of early Christian collective memories.